Illustrated Physiology. - Mackenna, B. R.; Callander, Robin, 1922-; McNaught, Ann B. (Churchill Livingstone, 1990)
This revised and updated edition has been designed to provide visual aids for those coming to the study of human physiology with no background of mammalian anatomy. It includes advances in topics such as the immune system, in the light of increased organ transplantation.
Keywords: Human physiology -- Outlines, syllabi, etc; Physiology -- atlases